PREVENTIVE MAINTENANCE CLOSED COOLING WATER PUMP TURBINE PADA PLTU PRIAMANAYA ENERGI KEBAN AGUNG LAHAT 2 X 135 MW - Satria, Miko; Nuramal, Agus; Mainil, Afdhal Kurniawan; Helmizar (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
Preventive maintenance is a maintenance and care activity carried out to prevent unexpected damage and to find conditions or circumstances that can cause production facilities to experience damage during the production process. The purpose of the research conducted by the author is to determine the implementation of preventive maintenance on the closed cooling water pump turbine at the Priamanaya Energi Keban Agung Lahat 2 x 135 MW PLTU, this research was conducted using the observation method or going directly to the field. This research resulted in that by carrying out preventive maintenance regularly and effectively on the closed cooling water pump at this PLTU, the company can ensure that they not only maintain smooth and efficient operations, but also reduce the risk of damage that can disrupt production.